2019
DOI: 10.1111/jcpp.13119
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of the interpersonal theory of suicide and effects of school‐based suicide prevention interventions in a multinational study of adolescents

Abstract: Background Predictions of two different models for suicide attempts (SA) over 12 months, as differentially impacted by specific school‐based suicide prevention interventions, were compared. These were as follows: (a) interpersonal theory (IPTS) and (b) a two‐pathway model, one path associated with externalizing symptoms and continuum of self‐harm behaviors, and the other with internalizing symptoms. Methods Self‐report questionnaires were completed by 11,110 high school students from ten EU countries enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
2
31
0
1
Order By: Relevance
“…Accumulating data indicate that youths with self‐harm histories are at increased risk of suicide deaths and increased risk of death by other unnatural causes, such as overdoses (Hawton et al., ; Morgan, Byrne, Boylan, McLearie, & Fitzpatrick, ). These results in conjunction with evidence reported in this issue that health risk behaviors such as substance abuse are associated with increased risk of SAs (Barzilay et al., ; King, Grupp‐Phelan et al., ) underscore the importance of clinical evaluation and monitoring of substance use in youths with suicide/self‐harm risk.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Accumulating data indicate that youths with self‐harm histories are at increased risk of suicide deaths and increased risk of death by other unnatural causes, such as overdoses (Hawton et al., ; Morgan, Byrne, Boylan, McLearie, & Fitzpatrick, ). These results in conjunction with evidence reported in this issue that health risk behaviors such as substance abuse are associated with increased risk of SAs (Barzilay et al., ; King, Grupp‐Phelan et al., ) underscore the importance of clinical evaluation and monitoring of substance use in youths with suicide/self‐harm risk.…”
Section: Introductionsupporting
confidence: 69%
“…Barzilay et al. () found that among YAM youths the effect of health risk behaviors (e.g., smoking, substance use, risky sexual behavior) on increasing the likelihood of repeated SAs (vs. no SAs) was reduced, relative to controls. Further, while the combination of baseline SI and self‐harm was associated with increased likelihood of repeat SAs over 12 months among control‐youths (no study intervention), this was not the case for youths receiving the SEYLE interventions (YAM; Screening by Professionals; Question, Persuade and Refer).…”
Section: Step 3: Community‐level Care Strategies and Universal Communitmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the program are long‐lasting when programs are maintained, but wane with discontinuation. These data combined with that from other programs such as the Youth Aware of Mental Health (YAM) school‐based intervention found to reduce SA rates (Wasserman et al., ; Barzilay et al., ) highlight the value of our science for developing effective suicide prevention initiatives.…”
mentioning
confidence: 87%
“…Barzilay et al. () confirm that suicidal ideation and self‐harm predict which youths in a school sample will attempt suicide and that health risk behaviors are associated with increased likelihood of repeat SAs 12 months later, suggesting one path to death by unnatural causes such as drug‐related deaths and accidents.…”
mentioning
confidence: 98%